2002
DOI: 10.1258/135763302320302154
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes, expectations and needs of elderly people in relation to e-health applications: results from a European survey

Abstract: We have carried out a survey of elderly people in Europe relating to e-health and telemedicine issues. Telephone-based interview techniques were used in 13 countries and face-to-face interviews were used in Ireland and Portugal, where there are significant numbers of houses without telephones. Altogether 9661 interviews were performed. Most respondents (65%) lived in rural areas or small towns; the remainder lived in suburban areas or large towns. Virtually all respondents (98%) had access to a television set.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Within the population groups, however, there have been different percentages of the Internet use reported. Depending on the sample involved (e.g., cardiac patients or those who have accessed primary care physician within a certain time period), 15% to 80% are reported to use the internet on a regular basis, with the elderly being least likely to do so [16,27,[34][35][36][37][38][39]56]. Consistent with the literature, our study showed that access to the internet was the lowest among the elderly, compared to those less than 35 years and those between 35 and 64 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the population groups, however, there have been different percentages of the Internet use reported. Depending on the sample involved (e.g., cardiac patients or those who have accessed primary care physician within a certain time period), 15% to 80% are reported to use the internet on a regular basis, with the elderly being least likely to do so [16,27,[34][35][36][37][38][39]56]. Consistent with the literature, our study showed that access to the internet was the lowest among the elderly, compared to those less than 35 years and those between 35 and 64 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Eng et al [30] suggest that access to health information and support online is a private road rather than a public highway for population groups such as the elderly. Specifically, studies from the United States of America (USA), European countries and Japan show that only 15% to 65% of those who access to the Internet use this medium to browse health information, with elderly being least likely to do so [16,27,[34][35][36][37][38][39][40]. A USA study of family practice clinic patients found that those greater than 65 years of age were less likely to access health information online, even after adjusting for the presence of a home computer and Internet access [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine (also known as telehealth) is defined as the provision of health services at a distance using a range of technologies [7]. The World Health Organization recommends telemedicine systems should be introduced where there is demand from patients [8]. With 1 in 3 people on the planet predicted to own a mobile phone by the end of 2016 [9], there is great enthusiasm among both patients and health care professionals to harness digital technologies to improve human health.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, determining the preferences or needs of potential users of tools is an important step in implementation [12-14]. Although studies have assessed patients’ preferences regarding the Internet in health care (eg, the preferred language on websites [15], the preferences of a Web-based intervention [16], preferences regarding social media and asthma patients [17], or the needs of elderly patients regarding eHealth [18]), less is known about the preferences or needs of consumers or the general public, especially regarding social media. A survey showed that 32% of all respondents (US adults) had used social media for health care purposes at one time or another [19].…”
Section: Introductionmentioning
confidence: 99%